Categorized Affective Pictures Database; tested on adults - rated appropriate for kids - Ilona Glebov-Russinov; Avishai Henik (Acta Psychologica)
The current study aimed to create a database of emotional pictures that would be suitable for studying participants of a wide age range (from the age of 5 years old). To create this database, experts evaluated whether pictures were suitable for young viewers. Next, we presented the pictures to a large group of adults and asked them to select each picture's emotional category, and then rate their confidence level and the intensity level of the pictures. An additional goal was to investigate the representation of all 10 emotional categories, reliability of norming data, and potential associations among emotional categories. We found that at least six emotions achieved a high consensus. Comparing our results with CAP-D data, collected in 2018, indicated high correlation. Last but not least, we identified coherent patterns of associations within both the positive and negative emotion domains, as well as distinct pairwise associations between specific emotions. To conclude, we provide adults' norms (dominant emotion, intensity ratings, etc.) regarding emotional categorization triggered by 566 pictures, which may be suitable for experiments across various age groups, including children.